Understanding free trade attitudes: Evidence from Europe - Martin Braml; Gabriel Felbermayr (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
Our paper shows that individual preferences for open-market policies are mainly shaped by trust in institutions and not economic self-interest. On the basis of the Eurobarometer, a comprehensive semiannual survey that monitors public opinion in EU Member States, we exploit data on attitudes towards the Transatlantic Trade and Investment Partnership (TTIP), free trade, protectionism, and globalization. We find that preferences for open-market trade policies cannot be sufficiently explained by variables that, according to classical trade theory, typically determine personal advantages. Nevertheless, rational considerations follow expected patterns, in particular when individuals express strong preferences. A spatial analysis at the European NUTS-2 level shows that measures of regional trade exposure and other macroeconomic determinants serve as well-suited predictors for the substantial cross-regional variation in the support for globalization. Country specific narratives are predominant drivers of individual open-market attitudes.
Keywords: F13; F53; F68; 330; international political economy; globalization; free trade attitudes